USE OF PROKEM LANGUAGE IN SOCIAL INTERACTION AT SATAP 7 BANAWA SELATAN SMPN (A sociolinguistic study) - Idrus (PT. Anagata Sembagi Education, 2024)
Prokem language is a unique form of communication often favored by teenagers today, though it originated among thugs as a means of secrecy. Over time, this language has transitioned into common usage among youth, including students in school settings. Teachers often express concern over its impact on student politeness. This research focuses on three key issues: 1) the forms of prokem language, 2) its formation process, and 3) its use among students at SMPN Satap 7 Banawa Selatan. The study aims to describe these aspects using sociolinguistic theory and a descriptive qualitative methodology. Data collection involved the referential method, with analysis carried out using distributional and equivalent methods. The findings reveal that prokem language appears in single and complex word forms. Its formation includes creating ew meanings for old words, inventing entirely new words, affixation, reduplication, abbreviations, and acronyms. Students use prokem language for various purposes, such as fostering familiarity, maintaining secrecy, expressing emotions like fear, anger, or pride, and even offering advice or ridicule. Despite these findings, further research is necessary to explore the relationship between prokem language, students' politeness, and their ability to speak with proper manners. This could provide deeper insights into its broader social and linguistic implications.